BALI PAINTING MARKET: A BRIEF HISTORY AND EXPLORATION OF VARIOUS FACTORS AFFECTING ITS DEVELOPMENT - Karja, I Wayan; Lei, Tai (Jurnal Kajian Seni, 2024)
This article presents a brief history of the art market in Bali and explores the various factors that have influenced its development. We also examine how local culture, the tourist market, village networks, government policies, and the global art market have shaped the trajectory of Balinese art. These forces include the assumption of local culture to art, the commercialization along with the opening of the tourist market, the local network based on village lives, the state policy to promote Balinese art and culture, and the effects brought by the booming of the global art market dominated by financial capital. Local concepts with cultural specificity are pivotal in our analysis, for example, the role culture plays in art practice nowadays and before, and what influence it brings to the transformation from art for religious purposes to cultural products for commerce. In conclusion, we highlight that the Balinese art market stands apart from other local art markets worldwide due to its close connection with Bali's reputation as a renowned tourist destination. The interplay of dynamic forces has shaped the market's growth, structure, and uniqueness over the years.